Visualisasi Perempuan Dalam Perspektif AL-Qur’an: Antara Teks dan Konteks - Aziz, Abdul (Universitas Islam Negeri Raden Intan Lampung, 2017)
One of the missions in Al-Qur'an is to uphold justice between men and women. But the justice and equality mission that is in the Qur'an which is